Makna Penderitaan sebagai Bagian dari Kehendak Tuhan bagi Umat-Nya - Tarukallo, Ebenhaezer (Institut Agama Kristen Negeri Palangka Raya, 2024)
Suffering, though undesirable, is something well known. Suffering is even an inseparable part of human life in general. Suffering due to illnesses, accidents, natural disasters, human crime, self-mistaken, war and other causes are present in various places and can happen to anybody. Including befalling the righteous. However, there are a handful of Christians who are so convinced that because they already believed in God, He must keep suffering away from their lives. Such conviction is not only they grasp for themselves but they also share it to others. Yet the facts show that it is not only those who do not believe in Jesus who experience hardship and suffering, but the ones who already believed as well. Even those who live righteous lives have no guarantee that they will escape suffering. To say that suffering is part of God's plan, some people approve, and the rest may disapprove. Those who approve that suffering is also part of God's sovereign will use Bible verses, the same as those who disapprove. So which one is true? Of course it is impossible for both to be true. Therefore through this paper, this matter will be reviewed. In writing this scientific paper, the writer used the method of literature research or literature review. The results of the author's research indicated that suffering, even though something undesirable by anyone, including believers, is part of God's will. Because only by God’s will and pemission, anything can happen.